2017
DOI: 10.1108/gm-09-2016-0159
|View full text |Cite
|
Sign up to set email alerts
|

Does gender make a difference in business performance?

Abstract: Purpose This paper aims toanalyse the difference in business performance and obstacles across male-owned versus female-owned enterprises in India. Design/methodology/approach This study is based on a comprehensive enterprise survey of 9,281 Indian firms operating in different regions of the country, conducted under the World Bank’s Enterprise Survey, 2014. The survey contains information on a variety of enterprise characteristics such as ownership, type of firms, size of firms, locations and age, performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 61 publications
(83 reference statements)
0
22
0
2
Order By: Relevance
“…Nevertheless, some scholars (Chell and Baines, 1998;Ahl, 2006;Coleman et al, 2019) strongly contend that structural, historical and cultural factors regarding enterprises of women are seldom discussed in the literature despite the significant effect of these issues on their businesses. As a consequence, gender power structures are made invisible, and no explanation is provided regarding how the social world is arranged (Ahl, 2004).…”
Section: Literature Review 21 Women and Entrepreneurshipmentioning
confidence: 99%
“…Nevertheless, some scholars (Chell and Baines, 1998;Ahl, 2006;Coleman et al, 2019) strongly contend that structural, historical and cultural factors regarding enterprises of women are seldom discussed in the literature despite the significant effect of these issues on their businesses. As a consequence, gender power structures are made invisible, and no explanation is provided regarding how the social world is arranged (Ahl, 2004).…”
Section: Literature Review 21 Women and Entrepreneurshipmentioning
confidence: 99%
“…This continuous interaction between interests and performance means that both must be measured and evaluated regularly as input into strategic e-business. Ali et al, 2017 in the results of the study showed that there were significant differences in the characteristics of companies belonging to men versus women-owned companies in terms of location, size, type and age. The results of the independent t-sample test showed significant differences in business performance across all male and female businesses in terms of annual sales growth, labor productivity growth and company capacity utilization.…”
Section: Literature Review Decision Making Capabilitymentioning
confidence: 85%
“…The findings from these studies are mixed overall, revealing that business performance depends upon the performance measure used and is tied closely to context, such that key controls often explain aggregate gender differences. While much of the research on gender patterns of business performance focuses on companies in highly industrialised countries (Da Vita, Mari and Poggesi 2014), studies on gender patterns in business performance in developing countries also find that women-owned businesses tend to perform favourably in terms of sales, profitability, and job creation when key factors such as industry and business age and size are considered (Ali and Shabir 2017).…”
Section: Discussionmentioning
confidence: 99%